Pattern of Respiratory Viruses among Pilgrims during 2019 Hajj Season Who Sought Healthcare Due to Severe Respiratory Symptoms - Salma M. Alsayed; Thamir A. Alandijany; Sherif A. El-Kafrawy; Ahmed M. Hassan; Leena H. Bajrai; Arwa A. Faizo; Eman A. Mulla; Lujain S. Aljahdali; Khalid M. Alquthami; Alimuddin Zumla; Esam I. Azhar (Pathogens, 2021)
The aim of our study was to define the spectrum of viral infections in pilgrims with acute respiratory tract illnesses presenting to healthcare facilities around the holy places in Makkah, Saudi Arabia during the 2019 Hajj pilgrimage. During the five days of Hajj, a total of 185 pilgrims were enrolled in the study. Nasopharyngeal swabs (NPSs) of 126/185 patients (68.11%) tested positive for one or more respiratory viruses by PCR. Among the 126 pilgrims whose NPS were PCR positive: (a) there were 93/126 (74%) with a single virus infection, (b) 33/126 (26%) with coinfection with more than one virus (up to four viruses): of these, 25/33 cases had coinfection with two viruses; 6/33 were infected with three viruses, while the remaining 2/33 patients had infection with four viruses. Human rhinovirus (HRV) was the most common detected viruses with 53 cases (42.06%), followed by 27 (21.43%) cases of influenza A (H1N1), and 23 (18.25%) cases of influenza A other than H1N1. Twenty-five cases of CoV-229E (19.84%) were detected more than other coronavirus members (5 CoV-OC43 (3.97%), 4 CoV-HKU1 (3.17%), and 1 CoV-NL63 (0.79%)). PIV-3 was detected in 8 cases (6.35%). A single case (0.79%) of PIV-1 and PIV-4 were found. HMPV represented 5 (3.97%), RSV and influenza B 4 (3.17%) for each, and Parechovirus 1 (0.79%). Enterovirus, Bocavirus, and M. pneumoniae were not detected. Whether identification of viral nucleic acid represents nasopharyngeal carriage or specific causal etiology of RTI remains to be defined. Large controlled cohort studies (pre-Hajj, during Hajj, and post-Hajj) are required to define the carriage rates and the specific etiology and causal roles of specific individual viruses or combination of viruses in the pathogenesis of respiratory tract infections in pilgrims participating in the annual Hajj. Studies of the specific microbial etiology of respiratory track infections (RTIs) at mass gathering religious events remain a priority, especially in light of the novel SARS-CoV-2 pandemic.